Expanding the Conceptual and Analytical Basis of Energy Justice: Beyond the Three-Tenet Framework - Lee, Joohee; Byrne, John (Frontiers in Energy Research, 2019)
Energy justice is now an established research topic in the field of energy policy. Despite the growing popularity of energy justice research, however, conceptual and analytical frameworks used in the field have remained limited. This paper reviews the prevailing three-tenet framework of energy justice which has shaped the current discourse based on the three dimensions – distributional, procedural, and recognition justice. As an effort to contribute to expanding the research agenda of energy justice problems, we propose a new understanding of the production of energy injustice by characterizing three institutionalized tendencies of dominant modern energy systems: 1) preference for large-scale technical systems and distancing of system designs from local decision-making processes; 2) centralization of energy production and concomitant distancing of supply from users; and 3) widespread ‘risk-taking’ tendencies portrayed by designers and proponents of current energy supply systems as a necessary ‘price to pay’ for technological innovation and social progress. We then connect these three tendencies to political, economic, and technical ideologies of modernism that often provide justifications for energy inequity: 1) top-down political and economic decision-making systems, 2) technical interpretation of sustainability, 3) specialist understanding of fairness, and 4) path dependency. Finally, we present an illustration of how this new conception of energy justice can be applied in practice using the case of South Korea’s nuclear power system and Seoul’s One Less Nuclear Power Plant Initiative.